Upaya Meminimalisir Angka Stunting di Desa Babakan Raden - Sari Ningsih; Uchaimid Biridlo'i Robb; Pretty Failasufa Aziza; Indri Yani (WINDRADI: Jurnal Pengabdian Masyarakat, 2024)
A community service activity was conducted by lecturers and students from the Faculty of Administrative Sciences at Krisnadwipayana University to raise awareness among the community in Babakanraden Village about the importance of minimizing stunting rates. The implementation method used outreach related to efforts to minimize stunting rates in Babakanraden Village. The three approaches used were preparation, outreach, and evaluation. The activity ran smoothly, and the community was actively involved in the outreach, as demonstrated by the interactive discussion between participants. Pre-test and post-test results indicated that the community was more knowledgeable and aware of how to prevent stunting and that they were increasingly concerned about food management. Going forward, education will continue to be conducted continuously to reduce stunting rates. Keywords: Stunting, Stunting Prevention, Key Role of the Community.